Flexural behaviour of reinforcement beam using slab deck permanent formwork - Muhammad Amir Sufi , Shukri (2013)
The use of slab deck permanent formwork method in reinforcement beam construction will give an effect on thier strength referring to the bonding of interfacial between cast in situ concrete and permanent formwork. In addition this method will minimized the construction handling, transportation and the number of workers. This paper presents the experimental result of the static loading effect on the reinforcement beam slab deck permanent formwork. Two different thickness (50mm and 75mm) with different material such as SikaGrout and normal plain concrete were incorporated as slab deck permanent formwork in reinforcement beam and a solid reinforcement beam without slab deck permanent formwork as the control specimen. Five number of sample, with dimension 150mm x 200mm x 3000mm, were tested, two of different thickness Sikagrout and normal concrete slab deck permanent formwork and one solid beam as control beam. The beams were subjected to four point loading test until failure. The findings of the experiment been shown that the beam with 75mm of SikaGrout slab deck permanent formwork were improved the performance of the structure. The observation made suggested that reinforcement beam with 75mm thickness of SikaGrout slab deck permanent formwork gave the optimum performance of the reinforced beam structure.